2003
DOI: 10.1074/jbc.m301485200
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Escherichia coli MobB in Molybdenum Cofactor Biosynthesis Based on the High Resolution Crystal Structure

Abstract: Two proteins, which are co-transcribed in Escherichia coli (MobA and MobB), are involved in the attachment of a nucleotide moiety to the molybdenum cofactor to form active molybdopterin guanine dinucleotide. Although not essential for this process, the dimeric MobB increases the activation of molybdoenzymes, incorporating this cofactor by a mechanism that is not understood. The structure of MobB has been elucidated in two crystal forms, one of which has provided a model at 1.9-Å resolution with R work and R fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In vivo, however, MobB, a GTP-binding protein interacting with MobA (20,49), may assist the GTP binding step. A docking model of MobA and MobB has suggested that GTP is bound to a shared binding site at the interface between both proteins (20). However, MobB did not enhance the activity of MGD formation under our assay conditions (data not shown).…”
Section: Sample Bvsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, however, MobB, a GTP-binding protein interacting with MobA (20,49), may assist the GTP binding step. A docking model of MobA and MobB has suggested that GTP is bound to a shared binding site at the interface between both proteins (20). However, MobB did not enhance the activity of MGD formation under our assay conditions (data not shown).…”
Section: Sample Bvsmentioning
confidence: 99%
“…In E. coli, GMP attachment to Mo-MPT is catalyzed by the MobA and MobB proteins, thereby forming MGD (19). MobA is crucial for this reaction and acts as a GTP:molybdopterin guanylyltransferase (14), whereas MobB is not essential (20). The type of Moco and ligand composition at the molybdenum atom divides the molybdoenzymes of E. coli into three families with the following coordination environment: the sulfite oxidase family (dioxo Mo-MPT with a protein cysteinate ligand), the xanthine oxidase family (mono-oxo MCD with a terminal sulfur ligand), and the dimethyl sulfoxide (DMSO) reductase family (bis-MGD with one oxo and one amino acid ligand) (1,3).…”
mentioning
confidence: 99%
“…S3). MobB functions downstream of MoaE in bacteria to form molybdopterin guanine dinucleotide common to enzymes of the DMSO reductase family (24,25). The MoaE homolog of H. volcanii and other archaea is likely to be linked to Ubl protein function, based on its amino acid sequence relationship to the large subunit of MPT synthase and its association with SAMP1 as detected by MS (20).…”
mentioning
confidence: 99%
“…Whereas MobA was shown to be essential for this reaction (18), the role of MobB still remains uncertain. From the crystal structure, it was postulated that MobB is an adapter protein that acts in concert with MobA to achieve the efficient biosynthesis and utilization of MGD (19).…”
mentioning
confidence: 99%